Psychosomatic health and sympathetic nervous adaptation of health professionals and the general population during the second covid-19 wave in Greece. between-group comparisons and regression analysis - Pilafas, Georgios; Lyrakos, Georgios (Health & Research Journal, 2021)
Background: Based on previous COVID-19 global literature, the second COVID-19 outbreak in Greece probably created a stressful environment for health professionals and the general population. It is likely that psychosomatic and sympathetic nervous symptoms increased in both groups. Aim: The study tests whether health professionals would present significantly higher levels of psychosomatic and sympathetic nervous symptoms, and whether several biopsychosocial criteria would predict psychosomatic symptoms overall. Material & Methods: 192 participants were recruited though the snowball strategy after the first domestic COVID-19 lockdown in Greece. Participants provided socio-demographic details, while they answered measurements regarding nervous adaptation (DASS-21), psychosomatics (PSSQ-29), resilience (NMRQ), self-efficacy (GSE) and personality (IPIP-50). The researchers performed independent t-tests, one-way ANOVAs, Pearson’s r correlation analysis and a multiple linear regression. Results: Health professionals experienced significantly less psychosomatic and sympathetic nervous symptoms compared to the general population, while none of the socio-demographic variables show between-groups differences. 10 out of 15 biopsychosocial variables were found significantly correlated with psychosomatic symptoms. The predictive model (Adjusted R2= .586) shows ‘stress’ (β= .242, p= .006), ‘anxiety’ (β= .494, p< .001) and ‘emotional stability’ (β= -.160, p= .004) to be significant predictors, excluding ‘gender’, ‘being a health professional’, ‘resilience’, ‘self-efficacy’ and ‘extraversion’. Conclusions: The findings contradict to previous studies regarding psychosomatic and sympathetic nervous symptoms in the COVID-19 era. Additionally, the prediction model is not consistent to the theories regarding resilience and self-efficacy. The present study provides much debate in the relevant fields of research.